COMPLIANCE BY DESIGN: REGISTRATION-TO-FILING PATHWAYS AND FRICTION POINTS - Zulfikar, Nirina Annara Vania; Ardhiansyah, Firman; Alfarishi, Muhammad Fazaro; Azizah, Elfrida Esti Nur; Ariyanti, Retno Dwi; Evazalina , Tessa (Journal of Strategic Behaviour Accounting, 2026)
This study examines the role of digital tax administration in shaping taxpayer compliance, with particular attention to the transition from registration to filing processes. Although digital systems such as e-registration, e-filing, and e-Billing have been implemented to simplify tax administration, taxpayers may still encounter administrative frictions that hinder the completion of compliance tasks. Using a compliance-by-design perspective, this study analyzes how procedural complexities, verification delays, and system-related issues create friction points along the compliance pathway. The study adopts a conceptual approach by mapping the taxpayer journey form registration to filing and identifying potential drop-off points that may reduce effective compliance. The findings indicate that administrative frictions within digital tax systems can disrupt the compliance process and increase the likelihood of incomplete filings. Therefore, improving system design, simplifying procedures, and strengthening user experience are essential to support a more seamless compliance process. This study contributes to the literature on digital tax administration by highlighting the importance of designing tax systems that minimize friction and facilitate taxpayer participation. The findings also provide policy insights for tax authorities seeking the enhance compliance through more user-centered digital services.